Diffusion-controlled bridging of the Au Island and Au core in Au@Rh(OH)3 core-shell structure - Zhang, Jie; Ren, Quan; Wang, Yun; Xiao, Ruixue; Chen, Hongyu; Xu, Wenjia; Feng, Yuhua (Frontiers in Chemistry, 2023)
Hybrid nanostructures have garnered considerable interest because of their fascinating properties owing to the hybridization of materials and their structural varieties. In this study, we report the synthesis of [Au@Rh(OH)3]-Au island heterostructures using a seed-mediated sequential growth method. Through the thiol ligand-mediated interfacial energy, Au@Rh(OH)3 core-shell structures with varying shell thicknesses were successfully obtained. On these Au@Rh(OH)3 core-shell seeds, by modulating the diffusion of HAuCl4 in the porous Rh(OH)3 shell, site-specific growth of Au islands on the inner Au core or on the surface of the outer Rh(OH)3 shell was successfully achieved. Consequently, two types of distinct structures, the Au island-on-[Au@Rh(OH)3] dimer and Au island-Au bridge-[Au@Rh(OH)3] dumbbell structures with thin necks were obtained. Further modulations of the growth kinetics led to the formation of Au plate-Au bridge-[Au@Rh(OH)3] heterostructures with larger structural anisotropy. The flexible structural variations were demonstrated to be an effective means of modulating the plasmonic properties; the Au–Au heterostructures exhibited tunable localized surface plasmon resonance in the visible-near-infrared spectral region and can be used as surface-enhanced Raman scattering (SERS) substrates capable of emitting strong SERS signals. This diffusion-controlled growth of Au bridges in the Rh(OH)3 shells (penetrating growth) is an interesting new approach for structural control, which enriches the tool box for colloidal nanosynthesis. This advancement in structural control is expected to create new approaches for colloidal synthesis of sophisticated nanomaterials, and eventually enable their extensive applications in various fields.